The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014 IEEE Aerospace Conference 2014
DOI: 10.1109/aero.2014.6836417
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric entry studies for Uranus

Abstract: The present paper describes parametric studies conducted to define the Uranus entry trade space. Two different arrival opportunities in 2029 and 2043, corresponding to launches in 202 1 and 2034, respectively, are considered in the present study. These two launch windows factor in the 84-year orbital period, significant axial tilt, and the wide ring system of Uranus. As part of this study, an improved engineering model is developed for the Uranus atmosphere. This improved model is based on reconciliation of da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Previous Neptune aerocapture studies have often been restricted to analysis of a single-point design with limited exploration of the underlying trade space. Multiple aerocapture studies have used a limited number of candidate interplanetary trajectories and vehicle designs to perform aerocapture systems analysis, and quantify the performance benefits compared to propulsive insertion [1,10,11,13,33]. The interplanetary trajectories are often optimized for propulsive insertion, and do not take into account the often differing requirements for aerocapture.…”
Section: Aerocapture Trade Space and Feasibility Analysismentioning
confidence: 99%
“…Previous Neptune aerocapture studies have often been restricted to analysis of a single-point design with limited exploration of the underlying trade space. Multiple aerocapture studies have used a limited number of candidate interplanetary trajectories and vehicle designs to perform aerocapture systems analysis, and quantify the performance benefits compared to propulsive insertion [1,10,11,13,33]. The interplanetary trajectories are often optimized for propulsive insertion, and do not take into account the often differing requirements for aerocapture.…”
Section: Aerocapture Trade Space and Feasibility Analysismentioning
confidence: 99%
“…While increasing the time required to reach the initial science orbit, this would also increase the delivered mass. A 2013 study at NASA Ames Research Center [8] examining the 2012 Planetary Science Decadal Survey (PSDS) [9] atmospheric entry probe mission at Uranus was expanded to include using aerocapture for the orbiter part of that mission and included that more realistic approach for the propulsive-only version of the mission. It concluded that the propulsively inserted version would require a launch mass 42% greater than the aerocaptured version, not 200% greater, but a project manager would still consider that increased payload capacity substantial.…”
Section: B Potential Benefits Of Aerocapturementioning
confidence: 99%
“…Multiple aerocapture studies have used a limited number of candidate interplanetary trajectories and vehicle designs to perform aerocapture systems analysis, and quantify the performance benefit compared to propulsive insertion. 1,[4][5][6][7] The interplanetary trajectories are often optimized for propulsive insertion, and do not take account for the differing requirements for aerocapture. While the increased delivered mass from using aerocapture has been quantified by multiple studies, analyses with a limited set of interplanetary trajectories are not representative of the broader aerocapture design space.…”
Section: The Need For a Unified Frameworkmentioning
confidence: 99%